The Effects of Thai Traditional Herbal Extracts on the Death of Cancer Cells - Boonyarat, Chantana; Jongpremkitpaisan, Bunthita; Chaiwasukul, Suwapak; Reubroycharoen, Prasert; Waiwut, Pornthip (Journal of Basic and Applied Pharmacology, 2020)
Cancer is a major health problem in Thailand; thus, there is a need to find and develop new active ingredients from plants for the inhibition of cancer cell proliferation. This paper reports an investigation into the effects on cancer cell proliferation of leaf extracts of five Thai traditional herbal plants: Cratoxylum formosum, Limnophila geoffrayi, Aegle marmelos, Syzygium gratum and Fagraea fragrans. The cytotoxic effects of the extracts on colon adenocarcinoma cells (HT-29), hepatocellular carcinoma cells (HepG2) and normal colon cells were measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the cell morphology was assessed by using phase-contrast microscopy. The signaling protein levels in apoptosis pathway were investigated by western blot analysis. The results showed that L. geoffrayi extract significantly induced the deaths of HT-29 cells (p<0.001) and HepG2 cells (p<0.05) with IC50 levels of 0.57±0.03 mg/mL and 0.57±0.01 mg/mL, respectively. C. formosum extract significantly induced HT-29 cell death (p<0.01), with an IC50 of 0.87±0.03 mg/mL. A. marmelos extract significantly induced HepG2 cell death (p<0.05) with an IC50 of 0.76±0.02 mg/mL. Moreover, these three extracts showed no significant cytotoxic effects towards the normal colon cells. In apoptosis pathway, L. geoffrayi and C. formosum extracts decreased the level of X-linked inhibitor of apoptosis protein (XIAP) as well as induced caspase-3 activation in HT-29 cells. In HepG2 cells, L. geoffrayi and A. marmelos extracts up-regulated death receptor 5 (DR5) level and inhibited the XIAP in correlation with caspase-3 activation. This study indicated that L. geoffrayi, C. formosum and A. marmelos leaf extracts at the concentrations up to 1 mg/mL induced cancer cell deaths without any cytotoxic effects on normal colon cells.